Detailed PSC formation in a two-dimensional chemical transport model of the stratosphere - D. Fonteyn; N. Larsen
A new two-dimensional zonal model of the stratosphere, based on a formulation in an isentropic framework, with complete chemistry has been coupled with a high resolution detailed microphysical model for polar stratospheric clouds (PSCs). The 2D model chemistry includes all presently known heterogeneous processes on sulfate aerosols and PSCs. The coupling of these two models, with inherently different time scales, is discussed. It is demonstrated that in order to obtain a realistic interrelationship between NO y and N 2 O an accurate simulation of the sedimentation by PSC particles is necessary. A good agreement of model PSC presence and observations is found for the Antarctic polar winter without the need to impose additional artificial temperature variations in the model. The calculated occurrence of polar stratospheric clouds and resulting heterogeneous chemistry during the Antarctic winter are discussed. Sensitivity of the polar stratospheric chemical composition and cloud formation for different perturbations is investigated by studying the effects of transport across the polar vortex boundary and heterogeneous processing by an enhanced sulfate aerosol load. The importance of including sedimentation for all cases is also discussed.